An ERK5–KLF2 signalling module regulates early embryonic gene expression and telomere rejuvenation in stem cells. Issue 23 (10th December 2021) - Brown, Helen A.; Williams, Charles A.C.; Zhou, Houjiang; Rios-Szwed, Diana; Fernandez-Alonso, Rosalia; Mansoor, Saria; McMulkin, Liam; Toth, Rachel; Gourlay, Robert; Peltier, Julien; Dieguez-Martinez, Nora; Trost, Matthias; et al.
Abstract : The ERK5 MAP kinase signalling pathway drives transcription of naïve pluripotency genes in mouse Embryonic Stem Cells (mESCs). However, how ERK5 impacts on other aspects of mESC biology has not been investigated. Here, we employ quantitative proteomic profiling to identify proteins whose expression is regulated by the ERK5 pathway in mESCs. This reveals a function for ERK5 signalling in regulating dynamically expressed early embryonic 2-cell stage (2C) genes including the mESC rejuvenation factor ZSCAN4. ERK5 signalling and ZSCAN4 induction in mESCs increases telomere length, a key rejuvenative process required for prolonged culture. Mechanistically, ERK5 promotes ZSCAN4 and 2C gene expression via transcription of the KLF2 pluripotency transcription factor. Surprisingly, ERK5 also directly phosphorylates KLF2 to drive ubiquitin-dependent degradation, encoding negative feedback regulation of 2C gene expression. In summary, our data identify a regulatory module whereby ERK5 kinase and transcriptional activities bi-directionally control KLF2 levels to pattern 2C gene transcription and a key mESC rejuvenation process.